Proposed new interior design for Nona Roguy Herbal Spa at No 2, Show Village, Jalan Timur 2/1, 71760 Bandar Enstek, Negeri Sembilan / Nur Hanisah Saadon - Saadon, Nur Hanisah (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Design is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose a new interior design for the interior of Nona Roguy Herbal Spa that is situated at No 2, Show Village, Jalan Timur 2/1, 71760 Bandar Enstek, Negeri Sembilan. This proposed spa centre is to attract users, mostly on women to try for themselves the treatment that the Nona Roguy offered, at the same time to promote their product successfully as they offered a Malay-based treatment and interiors, that is truly different from other spa range, that comes mostly from Malaysia. The target market for the users of this spa range product is women from all age and classes that are concern about their look and appearances, not forgetting to find those who are interested in trying a Malay-based spa treatment. Because of the customers that attend the sessions comes from different class of people, each room should be different so that it would match with the customers’ needs and it could give comfort to them while attending the sessions. Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the faith in the customers and the workers in Nona Roguy Herbal Spa. Connected to that, the chosen design style for Nona Roguy Herbal Spa is based on contemporary Malay design, goes all the way with the client’s needs as they want the spa centre to have the traditional Malay look and at the same time would attract the customers with different image that they would only get in Nona Roguy Herbal Spa. Before getting a desired design that is suitable with the client’s needs, some data analysis should be done where these analysis is on types of customers to attend the session, types of services offered, products of the brand, spaces to be concluded in the proposed area, operation time and information about other spas that use the same system in management, as the proposed spa. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.